Variations in Physical and Wood Anatomical Properties of Shorea of Malay Peninsula - Pande, P. K.; Negi, Krishna; Singh, Magan (Indian Forester, 2009)
The intra- and inter-species variations in the dimensions of different wood elements and wood density of Balau, White meranti (Meranti Pa'ang), Yellow meranti (Meranti damar hitam) and the Red meranti group of Malay Shorea were studied. Variance ratio (F) test indicated that intra-species differences of Shorea were non-significant for all the groups. Inter-species variations were significant for fibre length, fibre diameter, wall thickness and vessel element diameter for all the four groups except vessel element diameter for White meranti and fibre length for Yellow meranti. Significant variations in wood density were noticed for all the groups except in the Yellow meranti group (Î±=0.05). Crystals were present in parenchyma cells as solitary, in idioblast and/or also in short and long chains in the different species of Balau, Red and the Yellow meranti groups. In some species of Red meranti, viz. S. singkawang, prismatic crystals in chambered and non-chambered parenchyma cells were reported for the first time. Similarly crystals in ray cells were recorded in S. leptoclados, S. hemsleyana and S. macrantha. Crystals were not observed in the White meranti group. Silica bodies were a characteristic feature of White meranti group. The three types of normal axial inter-cellular canal, namely solitary, in broken tangential lines and long tangential lines were present in all the groups. Radial canal was present in the Yellow meranti and three species of the Red meranti group. Wall thickness, fibre diameter, wood density and vessel element length were positively correlated (Î±=0.05). Cluster analysis was done on the basis of qualitative and quantitative wood anatomical characters using binary matrix for all the groups. Two clusters were formed at 0% (Rescaled Distance Cluster Combine = 25) similarity level. One cluster grouped the species that belongs to White meranti, while another clustered the three groups viz. Balau, Red meranti and Yellow meranti. Yellow meranti further split from Balau and Red meranti at 6% similarity level. Red meranti and Balau clustered separately at 26% similarity level.